Monetary and foreign currency policy of the European Central Bank - Mladenović, Vladimir; Hadžić, Miroljub (The European Journal of Applied Economics, 2014)
The paper analyzes how successful the ECB has been in pursuing its monetary and foreign exchange policy, which is, at the same time, a complex issue and crucial for the justification of its existence. Firstly, the ECB is trying hard to keep up with the global crisis and to maintain the stability of the euro. The main task of the ECB is to keep inflation below 2% p.a. This paper demonstrates that the ECB has managed to retain inflation within the required limits for a significant period of time, except for few relatively short-lived exceptions. By managing an adequate monetary policy the ECB has successfully accomplished its goals in the period of reference, as demonstrated by inflation trend results, monetary aggregate M3, and the level of interest rates.